Organic Semiconducting Membranes: Freely Suspended, van der Waals Bound Organic Nanometer‐Thin Functional Films: Mechanical and Electronic Characterization (Adv. Mater. 16/2019). Issue 16 (16th April 2019) - Schaffroth, Lilian S.; Lenz, Jakob; Giegold, Veit; Kögl, Maximilian; Hartschuh, Achim; Weitz, R. Thomas
Abstract : Purely van der Waals bound films composed of organic small molecules can be suspended across gaps several hundreds of nanometers long, as shown by R. Thomas Weitz and co‐workers in article number1808309 . These solution‐crystallized freestanding films are used in fieldeffect transistors and are characterized with respect to their mechanical stability via local nanoindentation. Cover Image by Christoph Hohmann, Nanosystems Initiative Munich (NIM).